Glacier Evolution in a Changing World - Godone, Danilo (IntechOpen, 2017)
Glaciers have always played an important role in human history, and currently, they are carefully observed as climate change sentinels. Glacier melt rate is increasing, and its mass balance is continuously negative. This issue deserves accurate and in-depth studies in order to, adequately, monitor its state. This circumstance in fact endangers the water supply, affecting human settlements but also creating new environments allowing the colonization by pioneer communities and the formation of new landscapes. This book is subdivided into two main sections in order to deal with the two topics of worldwide research on glaciers and ecology in glacial environments. In the first one "Glaciers in the World," several reviews and studies are collected. It is an overview of glaciers, their state, and research carried out in different continents and contexts. The second section "Glacial Ecosystems" focuses, on the other hand, on glacier environments and ecological researches.